PELATIHAN BUDIDAYA IKAN NILA BERBASIS PAKAN PROBIOTIK DENGAN PENDAMPINGAN LAPANGAN: DAMPAK PADA PENGETAHUAN DAN PRAKTIK PAKAN DI POKDAKAN RAMPELOS, SANGIHE - Numisye Iske mose; Jetti Treslah Saselah; Magdalin Ulaan; Febryanti Ledanaung; Kenly Saworo (Universitas Mataram, 2026)
Limited knowledge in proper feed management can hinder the productivity of tilapia farming. Feed plays a crucial role as the main source of nutrients and energy needed to support the survival and growth of fish. One innovative approach to address this challenge is by utilizing probiotics and baker’s yeast as feed supplements. The primary challenge encountered by the partners is the low productivity of tilapia farming, which results from inefficient feed management and a lack of adequate knowledge about probiotic technology. Furthermore, this community service conducted to enhance the knowledge and skills of members of the Fish Farmers Group (Pokdakan) Rampelos in implementing probiotic-based tilapia cultivation. The methods used in this program consist of several stages: conducting surveys and interviews, preparing activities, delivering materials, carrying out practical sessions and mentoring, as well as evaluation. Previously, the partners had limited knowledge regarding the use of probiotics and baker’s yeast in tilapia farming. However, during the implementation, the members of Pokdakan Rampelos showed great enthusiasm and motivation, both in material delivery sessions and practical activities. The attendance rate during the activities averaged 90%, and members actively participated in discussions. Through mentoring and evaluation conducted by the service team, group members were able to properly implement the dosage of probiotics and baker’s yeast in feed. These results indicate that the technology introduced by the team was well-received and considered easy to apply, demonstrating its potential to improve feed efficiency and productivity in tilapia farming.